Effect of Lean Practices on Lead Time Reduction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents a study on the effect of Lean practices on lead time reduction. In this study, we have proposed the consideration of human, technical and environmental factors in the study of the impact of production scheduling and SMED on manufacturing lead time. Based on the fact that scheduling and SMED go well beyond a calculation function. From our point of view, it is preferable to broaden the field of study of this impact by going beyond the fields of mathematics, operational research and artificial intelligence. In this study, we propose to start from the idea that there are other factors that can influence the expected results, namely human, technical and environmental factors. To achieve this, we went through a literature review and then tried to validate our hypotheses through a quantitative study.